Islam ditinjau dari berbagai aspeknya - Harun Nasution (UI Press, 1985)
Oen, Jil. I=c.1-9; Jil.II=1-4/oen, jil. I=c.10-17/ir,jil.2,c.15/ ir,jil.1,c.18 ; jil.2,c.16/tr, jil.1=c.19/ tr, jil.2=c.17; jil. 1=c.20/tr, jil.2=c.18/tr, jil. 2=c.19; jil.1=c.21; jil. 2=c.20/oen, jil.1=c.22/ir,jil.1,c.23-25 ; jil.2,c.21-23/ir, jil.2,c.24/nis,jil.2,50